Multi-Omics Integration for Elucidating Herb–Gut Microbiota Interactions in Traditional Chinese Medicine - Grent Heward; Pavel Alvaorez; Hector L. Watkins; Davide M. Carpenter (International Journal of Clinical and Translational Medicine, 2026)
Traditional Chinese Medicine (TCM) exerts therapeutic effects through multi-component herbal formulations whose activities are mediated by host metabolic and immune networks and by biotransformations carried out by the gut microbiota. Multi-omics integration offers a system-level framework for disentangling these interactions, but the field still lacks robust architectures that connect genomic, transcriptomic, proteomic, metabolomic, and metagenomic measurements with clinically interpretable outcomes. This paper develops a systematic analysis of multi-omics integration for herb-gut microbiota research. It reviews the conceptual foundations of TCM systems pharmacology, the analytical challenges posed by data heterogeneity and scale, and the structural trade-offs in current computational platforms. The discussion emphasizes governance, FAIR data management, reproducibility, fairness across populations and experimental modalities, and sustainable deployment. It further examines how network-based modeling, community detection, and integrative pipelines can link chemical complexity to microbial function. Although multi-omics data generation has accelerated, integrative frameworks often treat TCM and microbiome research as separate domains, leading to fragmented evidence and limited clinical translation. By framing herb-gut microbiota interactions as a socio-technical infrastructure problem rather than a purely molecular puzzle, the paper provides a forward-looking agenda for academic, clinical, and regulatory stakeholders.